Fatal Adverse Events of Dabigatran Combined With Aspirin in Elderly Patients: An Analysis Using Data From VigiBase - Zhang, Qingxia; Ding, Qian; Yan, Suying; Yue, Qun-Ying (Frontiers in Pharmacology, 2021)
Introduction: The aim of this study was to analyze the clinical characteristics of fatal adverse events of dabigatran combined with aspirin in elderly patients, and to provide references for clinical rational use of drugs. Methods: Fatal adverse events caused by the combined use of dabigatran and aspirin in elderly patients aged over 75 were extracted from the WHO global database of individual case safety reports (VigiBase). Well-documented reports, vigiGrade completeness score ≥ 0.80, or with an informative narrative, were analyzed with a focus on the clinical features of the cases. Results: From 1968 up to 19 January 2020, there were 112 eligible reports in VigiBase from 13 countries, of which 33 were identified as well-documented. Of these 33, 19 were male (58%) and 14 were female (42%), the average age of the patients was 84 (75 to 95 years), with five cases of extreme weight (>100kg in 1 case, <50kg in 4 cases). There were 31 cases of death by internal bleeding (mainly 15 of gastrointestinal hemorrhage and 12 of intracranial hemorrhage) and two cases of the sudden death of unknown cause. Medication errors existed in 19 patients. The time to onset (TTO) was provided in 24 cases, ranging from two days to four years, and in 12 patients occurred within a month. Of the 31 patients with fatal bleeding events, 29 were associated with other factors that increase the risk of bleeding, such as diseases (hypertension, renal impairment, stroke, gastrointestinal related diseases, hypothyroidism, and cancer), drugs (antiplatelets, anticoagulants, thrombolytics, P glycoprotein substrates, non-steroidal anti-inflammatory drugs, hormones, selective serotonin reuptake inhibitors, and acetaminophen) and other factors (extreme body weight and alcohol consumption), and 21 of these contained two or more risk factors. Conclusion: The fatal adverse events associated with the combined use of dabigatran and aspirin in elderly patients were mainly serious bleeding events, which often occurred within one month. Most of these cases had medication errors and most of the patients had multiple diseases, medications, or other conditions at the same time that increase the risk of bleeding.